The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12942-022-00309-0
|View full text |Cite
|
Sign up to set email alerts
|

The geospatial and conceptual configuration of the natural environment impacts the association with health outcomes and behavior in children and adolescents

Abstract: Background Studies investigating associations between natural environments and health outcomes or health behaviors in children and adolescents yielded heterogenous results to date. This may be the result of different geospatial configurations of the natural environment and confounding characteristics of the study population. Thus, we investigated how the relationship between the natural environment and mental health, muscular fitness, and physical activity varies depending on the geospatial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Our study expands upon previous research by Nigg et al (2022) and van Den Berg et al (2010). Specifically, this study demonstrates that nearby environmental factors influence positive emotions within a larger buffer, with stronger effects during open periods.…”
Section: Moderating Effects Of Scale On Emotionssupporting
confidence: 91%
“…Our study expands upon previous research by Nigg et al (2022) and van Den Berg et al (2010). Specifically, this study demonstrates that nearby environmental factors influence positive emotions within a larger buffer, with stronger effects during open periods.…”
Section: Moderating Effects Of Scale On Emotionssupporting
confidence: 91%
“…These results indicate that the relationship between nature and health may be difficult to generalize across nature types. For example, a recent article showed that associations between the natural environment and mental health, physical fitness, and physical activity varied dependent on the geospatial configuration of the environment, with these different configurations representing different concepts of the natural environment ( Nigg, Niessner, Burchartz, Woll, & Schipperijn, 2022 ). Hence, to create effective nature-based solutions, it is important to understand which nature types are most effective in promoting health and health behaviors ( Bratman et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the background of livable life circle construction, stakeholders (people) in one life circle extract medical services (Numbers of bed and accessibility) from the medical facility in different levels according to the relevant rules. The scenarios vary from the different actions of stakeholders, including government investment, market investment, incurring the change of socioeconomic development and the political setting [20,43]. The spatial equality of medical service function involves the interrelationship between the demand for medical services and the supply of medical services.…”
Section: Conceptual Frameworkmentioning
confidence: 99%